Remote Control System for a VTOL UAV Stand with Computer Vision Elements - Reut, Dmytro; Tsukanov, Oleh (Моделювання, керування та інформаційні технології, 2025)
This work presents a remote control system for a vertical take-off and landing unmanned aerial vehicle (VTOL UAV) stand, implemented using the ESP32 microcontroller. The system provides control of actuators and aviation lights through a local web interface via a Wi-Fi connection. Additionally, a visualization subsystem was developed, including a camera with remote positioning capabilities and a human silhouette recognition algorithm using computer vision tools. The processed video stream is displayed on the web interface, with detected objects automatically highlighted by graphical bounding boxes. The proposed solution integrates hardware and software components, offering intuitive control and basic computer vision functions to enhance system functionality.